2018
DOI: 10.15252/embj.201798878
|View full text |Cite
|
Sign up to set email alerts
|

α‐Synuclein stimulation of monoamine oxidase‐B and legumain protease mediates the pathology of Parkinson's disease

Abstract: Dopaminergic neurodegeneration in Parkinson's disease (PD) is associated with abnormal dopamine metabolism by MAO-B (monoamine oxidase-B) and intracellular α-Synuclein (α-Syn) aggregates, called the Lewy body. However, the molecular relationship between α-Syn and MAO-B remains unclear. Here, we show that α-Syn directly binds to MAO-B and stimulates its enzymatic activity, which triggers AEP (asparagine endopeptidase; legumain) activation and subsequent α-Syn cleavage at N103, leading to dopaminergic neurodegen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
68
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(73 citation statements)
references
References 64 publications
5
68
0
Order By: Relevance
“…For instance, DOPEGAL and MAO-A levels are elevated 2.8- and 3.6-fold in AD LC neuronal cell bodies compared to controls (24), while MAO-B expression and activity are higher in multiple brain regions and cell types in AD (41, 42). While both MAO-A and MAO-B were capable of increasing AEP activity, Tau N368 cleavage, and cell death in our experiments, we favor MAO-A as the main driver of DOPEGAL production in vivo , with MAO-B playing a greater role generating the neurotoxic DA metabolite DOPAL in PD (21, 43) (Figure 7); that said, confirming this hypothesis will require additional experiments.…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…For instance, DOPEGAL and MAO-A levels are elevated 2.8- and 3.6-fold in AD LC neuronal cell bodies compared to controls (24), while MAO-B expression and activity are higher in multiple brain regions and cell types in AD (41, 42). While both MAO-A and MAO-B were capable of increasing AEP activity, Tau N368 cleavage, and cell death in our experiments, we favor MAO-A as the main driver of DOPEGAL production in vivo , with MAO-B playing a greater role generating the neurotoxic DA metabolite DOPAL in PD (21, 43) (Figure 7); that said, confirming this hypothesis will require additional experiments.…”
Section: Discussionsupporting
confidence: 48%
“…Previous studies show that physiological concentrations of DOPAL trigger the formation of α-Syn oligomers and aggregates in both a cell-free system and in cell culture, and produce cytotoxicity in vitro and in vivo . We recently reported that DOPAL activates AEP in dopaminergic neurons and leads to α-synuclein N103 cleavage by AEP, resulting in its aggregation and dopaminergic neuronal degeneration in the SN (21). Thus, DOPAL-α-Syn interactions may underlie the selective vulnerability of DA neurons in Parkinson’s disease (3539), and we suspected that a similar interaction might occur between DOPEGAL and Tau in AD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TUNEL and LDH analysis revealed that both MAO-A and MAO-B overexpression significantly activated AEP, increased Tau N368 cleavage, and magnified Tau neurotoxicity as measured by TUNEL, LDH, and loss of the catecholaminergic marker tyrosine hydroxylase (TH) (Supplemental Figure 3). By contrast, preventing DOPEGAL production by siRNA knockdown of DBH attenuated AEP activation and Tau-triggered cell we reported that AEP is activated by 3,4-dihydroxyphenylacetaldehyde (DOPAL), a highly toxic and oxidative dopamine (DA) metabolite, in the substantia nigra (21). Active AEP subsequently cleaves α-synuclein at N103 and promotes its aggregation and dopaminergic neuronal loss, leading to motor dysfunction in animal models of Parkinson's disease (PD) (22).…”
Section: Norepinephrine Metabolite Dopegal Activates Aep and Pathologmentioning
confidence: 99%
“…PINK1 specific modification of TH at the mitochondrial membrane or at MAMs provides addition burden to dopaminergic neurons and the PD gene product α-synuclein has previously been implicated in TH 17 regulation at mitochondrial-ER contact sites 88 . Parkin is known to suppress MAO 89 , a mitochondrial anchored enzyme responsible for dopamine degradation and mitochondrial DNA damage 90 and which is implicated in the pathogenesis of PD 91 .…”
Section: Discussionmentioning
confidence: 99%